VIGILÂNCIA, DADOS E PODER: A NOVA DIMENSÃO DOS DIREITOS COLETIVOS NA SOCIEDADE ALGORÍTMICA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The algorithmic society introduces a new regime of power grounded in surveillance and the exploitation of data on a global scale, establishing dynamics that reshape contemporary political, economic, and legal structures. This article analyzes the structural transformations that this model imposes on collective rights, examining in depth the intersections among technology, sovereignty, and citizenship within an increasingly automated decision-making environment. From an interdisciplinary perspective, it discusses how surveillance capitalism converts information into an instrument of social, economic, and political control, and how algorithmic governance challenges traditional legal categories such as responsibility, imputation, and legitimacy. It is argued that the effective protection of collective rights requires a critical reinterpretation of contemporary constitutionalism, grounded in the ethics of transparency, informational self-determination, social co-responsibility, and the creation of normative mechanisms capable of limiting the concentrating and asymmetric effects of automated systems.Keywords: Algorithmic Society; Surveillance; Collective Rights.